Leptin Signaling in the Ovary of Diet-Induced Obese Mice Regulates Activation of NOD-Like Receptor Protein 3 Inflammasome - Adamowski, Marek; Wołodko, Karolina; Oliveira, Joana; Castillo-Fernandez, Juan; Murta, Daniel; Kelsey, Gavin; Galvão, António M. (Frontiers in Cell and Developmental Biology, 2021)
Obesity leads to ovarian dysfunction and the establishment of local leptin resistance. The aim of our study was to characterize the levels of NOD-like receptor protein 3 (NLRP3) inflammasome activation in ovaries and liver of mice during obesity progression. Furthermore, we tested the putative role of leptin on NLRP3 regulation in those organs. C57BL/6J female mice were treated with equine chorionic gonadotropin (eCG) or human chorionic gonadotropin (hCG) for estrous cycle synchronization and ovary collection. In diet-induced obesity (DIO) protocol, mice were fed chow diet (CD) or high-fat diet (HFD) for 4 or 16 weeks, whereas in the hyperleptinemic model (LEPT), mice were injected with leptin for 16 days (16 L) or saline (16 C). Finally, the genetic obese leptin-deficient ob/ob (+/? and −/−) mice were fed CD for 4 week. Either ovaries and liver were collected, as well as cumulus cells (CCs) after superovulation from DIO and LEPT. The estrus cycle synchronization protocol showed increased protein levels of NLRP3 and interleukin (IL)-18 in diestrus, with this stage used for further sample collections. In DIO, protein expression of NLRP3 inflammasome components was increased in 4 week HFD, but decreased in 16 week HFD. Moreover, NLRP3 and IL-1β were upregulated in 16 L and downregulated in ob/ob. Transcriptome analysis of CC showed common genes between LEPT and 4 week HFD modulating NLRP3 inflammasome. Liver analysis showed NLRP3 protein upregulation after 16 week HFD in DIO, but also its downregulation in ob/ob−/−. We showed the link between leptin signaling and NLRP3 inflammasome activation in the ovary throughout obesity progression in mice, elucidating the molecular mechanisms underpinning ovarian failure in maternal obesity.